Optimizing banana corm-based local microorganisms for reduced NPK fertilization in pak choi (Brassica rapa) - JHON HARDY PURBA; I GUSTI MADE SUARMIKA; PUTU SHANTIAWAN PRABAWA (Smujo International, 2026)
Abstract. Purba JH, Suarmika IGM, Prabawa PS. 2026. Optimizing banana corm-based local microorganisms for reduced NPK fertilization in pak choi (Brassica rapa). Asian J Agric 10 (1): g100145. https://doi.org/10.13057/asianjagric/g100145. This study evaluated the effectiveness of banana corm-based local microorganisms (MOL) in reducing inorganic NPK fertilizer, particularly nitrogen, phosphorus, and potassium, inputs while maintaining pak choi (Brassica rapa) productivity, as measured by fresh and oven-dry biomass. This study quantitatively evaluates MOL × NPK interactions and identifies the agronomic optimum MOL dose using regression analysis, a topic that has rarely been addressed in previous MOL studies. The experiment was conducted from December 2023 to February 2024 in a lowland tropical agroecosystem in Bali, Indonesia, using a factorial Randomized Complete Block Design with two factors: three MOL doses (0, 30, and 60 mL polybag-¹) and four NPK levels (100%, 75%, 50%, and 25% of the recommended dose). Growth and yield parameters included plant height, leaf number, leaf area, and fresh and oven-dry biomass of shoots, roots, and total plants. Analysis of variance showed that MOL application significantly affected leaf area, root biomass, and total biomass (p < 0.05), whereas NPK level alone was not significant. However, a significant MOL × NPK interaction was observed for root and total biomass (p < 0.05). The 30 mL MOL treatment combined with 50-75% NPK produced the highest biomass, indicating a synergistic effect and allowing up to a 50% reduction in inorganic NPK fertilizer without loss of productivity. Quadratic regression analysis identified an agronomic optimum MOL dose of approximately 33 mL polybag-¹ under reduced NPK conditions (R² = 0.82). This study provides quantitative evidence that integrating MOL with reduced NPK fertilization improves nutrient-use efficiency in pak choi cultivation. However, the results are based on a short-term pot experiment, and field-scale validation is required. The integration of locally available organic microbial inputs offers a promising approach to support more sustainable and cost-effective vegetable production systems.